Hold the phone: The short- and long-run impacts of connecting Indian women to digital technology - Giorgia Barboni; Anwesha Bhattacharya; Erica Marie Field; Rohini Pande; Natalia Rigol; Simone Schaner; Aruj Shukla; Charity Troyer Moore (Yale University, Economic Growth Center, 2024)
Access to smartphones and mobile internet is increasingly necessary to participate in the modern economy. Yet women significantly lag men in digital access, especially in lower-income settings with gender gaps that span other dimensions - and where digital gaps threaten to deepen existing analog inequities. We study the short- and long-term effects of a large-scale state-sponsored program in India that aimed to close digital gender gaps by transferring free smartphones to women while constructing 4G towers to bring rural areas online. The program was well implemented, reversing gender gaps in smartphone ownership in the short run. However, many women lost ownership and gender gaps in use quickly worsened as men made use of the new phones. Nearly 5 years after the program began, we find limited evidence of persistent effects across a range of outcomes, including phone ownership and use, gender norms, access to information, and local economic activity, although we do find some evidence of sectoral reallocation in the labor market. Despite widespread increase in smartphone adoption across households, digital gender gaps persist and were not affected by the program. Our findings suggest that in gender-unequal, resource-constrained settings, addressing affordability alone may not close digital gender gaps.
Keywords: 330